2011
DOI: 10.1007/s11249-011-9760-3
|View full text |Cite
|
Sign up to set email alerts
|

Mild Wear Prediction of Boundary-Lubricated Contacts

Abstract: In this paper, a wear model is introduced for the mild wear present in boundary-lubricated systems protected by additive-rich lubricants. The model is based on the hypothesis that the mild wear is mainly originating from the removal of the sacrificial layer formed by a chemical reaction between the base material and the additive packages present in the lubricant. By removing a part of this layer, the chemical balance of the system is disturbed and the system will try to restore the balance for which it uses ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Bosman and Schipper [36] proposed a compensation factor for the hardness as a function of temperature. The hardness at a given temperature can then be obtained by using the initial hardness given in Fig.…”
Section: Tribo-film Growth and Its Mechanical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bosman and Schipper [36] proposed a compensation factor for the hardness as a function of temperature. The hardness at a given temperature can then be obtained by using the initial hardness given in Fig.…”
Section: Tribo-film Growth and Its Mechanical Modelmentioning
confidence: 99%
“…The concentration in the tribo-film will be highest close to the 'interface with the substrate material' and lower close to the 'free surface.' The loss of substrate material due to tribo-film wear will therefore decrease with increasing film thickness [9,36]. The following relation was used to calculate the concentration as a function of the tribo-film thickness h:…”
Section: Macroscale Contact With Roughnessmentioning
confidence: 99%
“…Bosman et al [33,34] used diffusion reactions to capture the growth of tribofilm on the surfaces. They proposed a new wear model that considers partial removal of the tribofilm responsible for mild wear of boundary lubricated contacts.…”
Section: Wear Predictionmentioning
confidence: 99%
“…A model developed by Bosman et al [31] proposed a numerical formulation for mild wear prediction under boundary lubrication conditions for ZDDP on steel surfaces. They suggested that ZDDP chemically reacted layers are the main mechanisms responsible for protecting boundary-lubricated systems, and when these layers are worn off, the system will restore the balance and the substrate will react with the oil to produce a tribofilm.…”
Section: Introductionmentioning
confidence: 99%